IMPLEMENTASI SISTEM INFORMASI APRON MOVEMENT CONTROL DI BANDAR UDARA INTERNASIONAL SULTAN HASANUDDIN MAKASSAR - Jumlad, Walid; Nurhalisa, Nurhalisa (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
Apron Movement Control (AMC) officers play a crucial role in maintaining smooth airport operations by using the Apron Movement Control Information System. The Information System supports the work of AMC officers at Sultan Hasanuddin International Airport to organize the planning and arrangement of aircraft movements that will support the creation of operations without obstacles or delays in accordance with flight schedules and all information. This research uses a qualitative approach, data obtained from observations, interviews and documentation. Furthermore, the data that has been collected is tested for validity using triangulation techniques to draw conclusions so that the research results can be accounted for validity and credibility. The results of the study prove that the Information System helps in supporting the operations carried out by the AMC unit. The Information System consists of SIOPSKOM which assists the AMC unit in recording flight data and commercial billing systems for the aeronautical/flight side. Schedule Flight helps the AMC unit in updating the daily schedule and season schedule, it can also be used to create gate placement plans, baggage belt placement plans. Aircraft Turnaround View (ATV) helps the AMC unit in flight operations from take-off to landing of aircraft. Parking Stand Management can assist the AMC unit in determining the aircraft parking lot based on the type of aircraft, gate and for repositioning aircraft parking according to instructions from ground handling. Obstacles in implementing the Information System used by the AMC Unit in this study found system updates that experienced obstacles and obstacles as well as delays in the airline in providing flight schedules and the system has not been fully implemented.